Long- and Short-Run Components of Factor Betas: Implications for Stock Pricing - Hossein Asgharian; Charlotte Christiansen; Ai Jun Hou; Weining Wang (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2020)
We propose a bivariate component GARCH-MIDAS model to estimate the long- and short-run components of the variances and covariances. The advantage of our model to the existing DCC-based models is that it uses the same form for both the variances and covariances and that it estimates these moments simultaneously. We apply this model to obtain long- and short-run factor betas for industry test portfolios, where the risk factors are the market, SMB, and HML portfolios. We use these betas in cross-sectional analysis of the risk premia. Among other things, we find that the risk premium related to the short- run market beta is significantly positive, irrespective of the choice of test portfolio. Further, the risk premia for the short-run betas of all the risk factors are significant outside recessions.
Keywords: G12; C58; C51; 330; long-run betas; short-run betas; risk premia; business cycles; component GARCH model; MIDAS